2012
DOI: 10.1523/jneurosci.5599-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Trk Activation of the ERK1/2 Kinase Pathway Stimulates Intermediate Chain Phosphorylation and Recruits Cytoplasmic Dynein to Signaling Endosomes for Retrograde Axonal Transport

Abstract: The retrograde transport of Trk containing endosomes from the axon to the cell body by cytoplasmic dynein is necessary for axonal and neuronal survival. We investigated the recruitment of dynein to signaling endosomes in rat embryonic neurons and PC12 cells. We identified a novel phospho-serine on the dynein intermediate chains (IC) and we observed a time-dependent neurotrophin-stimulated increase in intermediate chain phosphorylation on this site in both cell types. Pharmacological studies, over-expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(111 citation statements)
references
References 80 publications
8
101
2
Order By: Relevance
“…Dynein IC1 can also interact with the G␤␥ subunit, which plays a central role in G-protein signaling and is involved in cell division, vesicle trafficking, and signal integration (74). The Trk-ERK1/2-stimulated phosphorylation of dynein IC is required for regulation of dynein activity and affects certain cellular events, such as microtubule-dependent sliding and mitosis (75)(76)(77). The middle part of IC1 consists of repetitive sequences homologous to the sequence of the nucleoside diphosphate kinase (NDPK), indicating that IC1 may function as an NDPK that regulates RNA, DNA, and polysaccharide synthesis (78)(79)(80).…”
Section: Discussionmentioning
confidence: 99%
“…Dynein IC1 can also interact with the G␤␥ subunit, which plays a central role in G-protein signaling and is involved in cell division, vesicle trafficking, and signal integration (74). The Trk-ERK1/2-stimulated phosphorylation of dynein IC is required for regulation of dynein activity and affects certain cellular events, such as microtubule-dependent sliding and mitosis (75)(76)(77). The middle part of IC1 consists of repetitive sequences homologous to the sequence of the nucleoside diphosphate kinase (NDPK), indicating that IC1 may function as an NDPK that regulates RNA, DNA, and polysaccharide synthesis (78)(79)(80).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of dynein subunits has also been implicated in dynein regulation (Dillman and Pfister, 1994;Lin et al, 1994;Vaughan et al, 2001), with some examples showing that phosphorylation can inhibit or enhance dynein binding to organelles or some cargoes (Mitchell et al, 2012). Atypical PKC (aPKC) can phosphorylate DICs, regulating their binding with paxillin, thus controlling the focal adhesion disassembly (Rosse et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Two dynein subunits, intermediate chains 1 and 2 (DIC1 and DIC2, also known as DYNC1I1 and DYNC1I2) have been implicated in dynein binding to both aggregated proteins (Xu et al, 2013) and cellular organelles (Pfister et al, 2006;Mitchell et al, 2012) for retrograde transport to aggresomes. The adaptor protein SQSTM1 (Okatsu et al, 2010) has also been implicated in aggresome formation by contributing to the transport of both ubiquitylated (Behl, 2011) and nonubiquitylated proteins (Watanabe and Tanaka, 2011).…”
Section: Sqstm1 Interacts With Dyneinmentioning
confidence: 99%
See 1 more Smart Citation
“…Many other lines of research support the view that kinesin-and dynein-mediated transport is modulated by phosphorylation. For example, ERK1/2 phosphorylation of dynein intermediate chain (DIC) recruits cytoplasmic dynein to signaling endosomes for retrograde transport in axons (Mitchell et al, 2012). Moreover, recent studies in Caenorhabditis elegans have shown that two cyclin-dependent kinases, PCT-1 and CDK-5, directly polarize trafficking of presynaptic components by inhibiting dyneinmediated retrograde transport and setting the balance between anterograde and retrograde motors (Ou et al, 2010).…”
Section: Motor Adaptors As Regulators Of Motor Activitymentioning
confidence: 99%